History of research concerning the ependyma: a view from inside the human brain - Del Bigio, Marc R. (Frontiers in Cellular Neuroscience, 2024)
The history of research concerning ependymal cells is reviewed. Cilia were identified along the surface of the cerebral ventricles c1835. Numerous anatomical and histopathological studies in the late 1800’s showed irregularities in the ependymal surface that were thought to be indicative of specific pathologies such as syphilis; this was subsequently disproven. The evolution of thoughts about functions of cilia, the possible role of ependyma in the brain-cerebrospinal fluid barrier, and the relationship of ependyma to the subventricular zone germinal cells is discussed. How advances in light and electron microscopy and cell culture contributed to our understanding of the ependyma is described. Discoveries of the supraependymal serotoninergic axon network and supraependymal macrophages are recounted. Finally, the consequences of loss of ependymal cells from different regions of the central nervous system are considered.